2017
DOI: 10.1111/acel.12678
|View full text |Cite
|
Sign up to set email alerts
|

Caloric restriction stabilizes body weight and accelerates behavioral recovery in aged rats after focal ischemia

Abstract: SummaryObesity and hyperinsulinemia are risk factors for stroke. We tested the hypothesis that caloric restriction, which reduces the incidence of age‐related obesity and metabolic syndrome, may represent an efficient and cost‐effective strategy for preventing stroke and its devastating consequences. To this end, we placed aged, obese Sprague‐Dawley aged rats on a calorie‐restricted diet for 8 weeks prior to the experimental infarction. Stroke in this animal model caused a progressive decrease in weight that r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 43 publications
(46 reference statements)
1
25
0
Order By: Relevance
“…Previous studies in animal models of focal cerebral ischemia found that undernutrition reduces brain injury [7-9, 16, 17], whereas other studies in models of focal or global ischemia showed that ischemic injury was unchanged by undernutrition [10][11][12][13]. A variety of studies in models of focal or global ischemia observed a significant reduction of stroke-induced neurological deficits [7][8][9][10][11], whereas other studies, again in focal or global ischemia, noted exacerbated or unchanged deficits [12][13][14][15]. Major differences in these studies relate to the type of undernutrition.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies in animal models of focal cerebral ischemia found that undernutrition reduces brain injury [7-9, 16, 17], whereas other studies in models of focal or global ischemia showed that ischemic injury was unchanged by undernutrition [10][11][12][13]. A variety of studies in models of focal or global ischemia observed a significant reduction of stroke-induced neurological deficits [7][8][9][10][11], whereas other studies, again in focal or global ischemia, noted exacerbated or unchanged deficits [12][13][14][15]. Major differences in these studies relate to the type of undernutrition.…”
Section: Discussionmentioning
confidence: 99%
“…Major differences in these studies relate to the type of undernutrition. As such, undernutrition was induced by (a) reducing food access to 60 or 70% of the average amount of control animals for 4 weeks to 3 months [8,10,13,16], (b) reducing food protein content to 0 to 12% for 6 days to 4 weeks [9,12,14,15], or (c) intermittent fasting on alternate days or twice per week for one to several months [7,11,17]. While reducing the amount of food access similarly reduces protein and energy consumption, the reduction of protein content to 0-2% results in a reduction in the total amount of food ingested, since the animals refuse this chow [9,12,14,15].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations